Position of Indonesia in WTO Reform - Syadullah, Makmun; Dwiyanti, Adwiena (International Journal of Economics and Financial Issues, 2019)
The issue of WTO reforms launched by the European Union and Canada in July 2018 is an, the issue of Most Favored Nation, the problem of overseeing the opportunity for developing countries to fight for their interests. This reform is expected to have a positive impact on the trade of developing countries. In addition, it is also expected to bring positive changes to the multilateral trading system and is expected to be able to accommodate the interests of developed and developing countris. This paper aims to analyze issues related to WTO reform, the effectiveness of WTO policies towards developing countries and formulate the position of developing countries in WTO reform. Several issues faced by developing countries that need to be fought for in WTO reform include: problems with market access and legal flexibility implementation, administration and operation of closed agreements, implementation of S & D provisions, public stockholding issues, problems special safeguard mechanism, problems with Appallate Body-WTO membership, and problem of digital commerce. Keywords: international trade, WTO, Interregional Trade JEL Classifications: F1, F13, F14, F15 DOI: https://doi.org/10.32479/ijefi.8890